Bioimpact on weathering steel surfaces: Oxalates formation and the elucidation of their origin. (October 2015) - Aramendia, Julene; Gomez-Nubla, Leticia; Bellot-Gurlet, Ludovic; Castro, Kepa; Arana, Gorka; Madariaga, Juan Manuel
Abstract: This study was carried out to elucidate the causes of irregularities and discolorations on the surface of parts of a weathering steel sculpture which had been in contact with wood pallets. Non-destructive analysis of the samples by Raman spectroscopy revealed the presence of iron oxalates and calcium oxalates. Thermodynamic modeling suggested that the detected oxalates were produced by the reaction of oxalic acid, a potential metabolite excreted by microorganisms, and elements present in the steel surface such as iron. Carotenoids including β-carotene and astaxanthin, biomarkers for a large number of prokaryotic and eukaryotic microorganisms, were also detected in samples. Highlights: Biological signs have been found in weathering steel surface. Carotenoids and oxalates confirm biological life in the surface. Different hydration forms of calcium oxalates can be damaging the steel surface. Iron oxalates were formed from the reaction among oxalic acid and the alloy iron.